In search of memory - Ngwe, Xian Tian (2019)
In recent years, people have become increasingly unsatisfied with what they have. Caught up in the rat race, they find themselves not having time to reflect on their past, or to slow down and appreciate the beauty of the simple things in life. In Search of Memory is a visual retrospection of the author’s past memories. It explores how a visual approach on life review therapy can be used to increase life satisfaction for young adults. Through reconstructing life stories and the re-evaluation of the fond memories to help re-frame her current difficulties, it serves to provide the therapeutic reflection on her thought patterns and behavior. It hopes to inspire others to reflect on their own past through self-discovery, by evoking nostalgia from collective memories.